(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, inaugurate interval-valued triangular neutrosophic fuzzy graph (IVTNFG) of SPP, which is drew on three-sided numbers and IVTNFG. Hear a genuine application is given an illustrative model for IVTNFG. Additionally Shortest way is determined for this model. This present Dijkstra’s Algorithm briefest way was checked through Python Jupiter Notebook (adaptation) programming.